2014
DOI: 10.3390/cancers6020708
|View full text |Cite
|
Sign up to set email alerts
|

The Role of STAT3 in Non-Small Cell Lung Cancer

Abstract: Persistent phosphorylation of signal transducer and activator of transcription 3 (STAT3) has been demonstrated in 22%~65% of non-small cell lung cancers (NSCLC). STAT3 activation is mediated by receptor tyrosine kinases, such as epidermal growth factor receptor (EGFR) and MET, cytokine receptors, such as IL-6, and non-receptor kinases, such as Src. Overexpression of total or phosphorylated STAT3 in resected NSCLC leads to poor prognosis. In a preclinical study, overexpression of STAT3 was correlated with chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
151
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 98 publications
3
151
1
Order By: Relevance
“…By contrast, silenceing STAT3 demonstrated more sensitive to the cytotoxic agents. Also, STAT3 plays a crucial role in chemotherapy [40]. The findings of a previous study suggested that DM at the time of diagnosis had no association with survival in patients with SCLC [41], although small cell lung cancer (SCLC) patients generally only survive for a short time anyway, and hence survival may not be affected by the presence of DM.…”
Section: Discussionmentioning
confidence: 87%
“…By contrast, silenceing STAT3 demonstrated more sensitive to the cytotoxic agents. Also, STAT3 plays a crucial role in chemotherapy [40]. The findings of a previous study suggested that DM at the time of diagnosis had no association with survival in patients with SCLC [41], although small cell lung cancer (SCLC) patients generally only survive for a short time anyway, and hence survival may not be affected by the presence of DM.…”
Section: Discussionmentioning
confidence: 87%
“…Signal transducer and activator of transcription 3 (Stat3) signaling is constitutively activated and associated with chemoresistance in NSCLC [10]. Inhibition of Stat3 signaling has been documented to sensitize A549 NSCLC cells to DNA damaging drugs doxorubicin and CDDP [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, targeting Stat3 has potential for prevention and treatment of cancers [17, 19]. Stat3 is persistently activated in NSCLC [14, 20], overexpression of Stat3 resulted in poor prognosis, thus, high activation of p-Stat3 was considered as a diagnostic marker in patients with NSCLC [16]. However, the potential role of this molecule in mediating the effect of ATL-1 has not been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of Stat3 promoted tumor growth through regulating the expression of genes involved in proliferation, apoptosis, and angiogenesis, among others [14, 15]. Several reports showed that inhibition of Stat3 suppressed the growth of cancer cells and enhanced the sensitivity to anticancer agents in several cancer types [16-18]. Thus, targeting Stat3 has potential for prevention and treatment of cancers [17, 19].…”
Section: Introductionmentioning
confidence: 99%